Rhopalomma stefaniae gen. et sp. n., the first ommatid beetle from the Upper Jurassic in Australia (Coleoptera: Archostemata: Ommatidae) - Ashman, Lauren G.; Oberprieler, Rolf G.; Ślipiński, Adam (Zootaxa, 2015)
The first Upper Jurassic fossil of the family Ommatidae (Coleoptera: Archostemata) from Australia is described and illustrated from a single specimen discovered at the Talbragar Fish Bed. Rhopalomma stefaniae gen. et sp. n. is classified in Ommatidae based on the length and insertion of the antennae, the tuberculate cuticle, the pattern of elytral striae, the complete epipleura and the presence of scutellary strioles. Due to the lack of preservation of crucial characters, Rhopalomma cannot be assigned to a subfamily and is therefore classified as Ommatidae incertae sedis. Rhopalomma fills an important gap in the fossil record of the family, indicating that Ommatidae occurred in Australia from the Lower Jurassic to the present day. Australia is the only place in the world where this family is found in both the fossil record and the living fauna.